Axonopathy in the Central Nervous System Is the Hallmark of Mice with a Novel Intragenic Null Mutation of Dystonin. Issue 1 (1st September 2016) - Seehusen, Frauke; Kiel, Kirsten; Jottini, Stefano; Wohlsein, Peter; Habierski, Andre; Seibel, Katharina; Vogel, Tanja; Urlaub, Henning; Kollmar, Martin; Baumgärtner, Wolfgang; Teichmann, Ulrike
Abstract: Dystonia musculorum is a neurodegenerative disorder caused by a mutation in the dystonin gene. It has been described in mice and humans where it is called hereditary sensory autonomic neuropathy. Mutated mice show severe movement disorders and die at the age of 3–4 weeks. This study describes the discovery and molecular, clinical, as well as pathological characterization of a new spontaneously occurring mutation in the dystonin gene in C57BL/6N mice. The mutation represents a 40-kb intragenic deletion allele of the dystonin gene on chromosome 1 with exactly defined deletion borders. It was demonstrated by Western blot, mass spectrometry, and immunohistology that mice with a homozygous mutation were entirely devoid of the dystonin protein. Pathomorphological lesions were restricted to the brain stem and spinal cord and consisted of swollen, argyrophilic axons and dilated myelin sheaths in the white matter and, less frequently, total chromatolysis of neurons in the gray matter. Axonal damage was detected by amyloid precursor protein and nonphosphorylated neurofilament immunohistology. Axonopathy in the central nervous system (CNS) represents the hallmark of this disease. Mice with the dystonin mutation also showed suppurative inflammation in the respiratory tract, presumably due to brain stem lesion-associated food aspiration, whereas skeletal muscles showed no pathomorphological changes. This study describes a novel mutation in the dystonin gene in mice leading to axonopathy in the CNS. In further studies, this model may provide new insights into the pathogenesis of neurodegenerative diseases and may elucidate the complex interactions of dystonin with various other cellular proteins especially in the CNS.